2021
DOI: 10.1038/s41423-021-00751-3
|View full text |Cite
|
Sign up to set email alerts
|

Microglia as hackers of the matrix: sculpting synapses and the extracellular space

Abstract: Microglia shape the synaptic environment in health and disease, but synapses do not exist in a vacuum. Instead, pre- and postsynaptic terminals are surrounded by extracellular matrix (ECM), which together with glia comprise the four elements of the contemporary tetrapartite synapse model. While research in this area is still just beginning, accumulating evidence points toward a novel role for microglia in regulating the ECM during normal brain homeostasis, and such processes may, in turn, become dysfunctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 342 publications
(561 reference statements)
1
94
0
Order By: Relevance
“…However, Aβ itself, but not tau, progressively impairs the capacity of these glial cells to eliminate damaged amyloid-containing presynaptic elements ( Sanchez-Mico et al, 2021 ). Besides, microglial cells are implicated in synaptic homeostasis as well, and the rate of maintenance/elimination of boutons or perineuronal nets might be altered due to amyloid exposition ( Hong et al, 2016 ; Crapser et al, 2020 , 2021 ). Soluble Aβ itself can induce synaptic alterations in the absence of plaques ( Lue et al, 1999 ; Dorostkar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Aβ itself, but not tau, progressively impairs the capacity of these glial cells to eliminate damaged amyloid-containing presynaptic elements ( Sanchez-Mico et al, 2021 ). Besides, microglial cells are implicated in synaptic homeostasis as well, and the rate of maintenance/elimination of boutons or perineuronal nets might be altered due to amyloid exposition ( Hong et al, 2016 ; Crapser et al, 2020 , 2021 ). Soluble Aβ itself can induce synaptic alterations in the absence of plaques ( Lue et al, 1999 ; Dorostkar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a focus on the hippocampus, as well as on cultured hippocampal neurons, electrophysiological alterations were observed when perineuronal nets were disrupted in vivo and in vitro [ 271 , 302 , 303 , 304 , 305 , 306 ]. Interestingly, there is a growing evidence that microglia are involved in the maintenance of perineuronal nets [ 307 ]. In disease models for Alzheimer’s and Huntington’s, a contribution of microglia to the loss of perineuronal nets could be proven [ 308 , 309 ].…”
Section: Interneuron-abnormalities In the Hippocampus Of Schizophreni...mentioning
confidence: 99%
“…We have consistently observed that elimination of microglia via colony stimulation factor 1 receptor (CSF1R) inhibitors 14 dramatically increases PNN coverage throughout the brain 15 18 . Furthermore, upon cessation of treatment with the CSF1R inhibitor PLX5622, microglia repopulate the brain and PNNs decrease back to basal levels 19 .…”
Section: Introductionmentioning
confidence: 99%